Enhancing Students’ Vocabulary Mastery using Spot It! Card Game in Distance Learning - Suci Ayu Kurniah P; Rusliana Rusliana; Erna Fitriani Pratiwi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This study aimed at finding the effectiveness of Spot it! Card Game in enhancing students’ English vocabulary mastery in distance learning. The research used a quasi-experimental research design. The participants were the second year students of SMA Pesantren Modern Datuk Sulaeman Palopo Bagian Putri which were divided into experimental group and control group consisted of 20 students in each group. The result indicates that the students of the experimental group have significant improvement of the mean score which is5,42 on Pre-test classified as Poor to 8,89 on Post-test classified as Very Good after given treatment using Spot It! Card Game. Meanwhile, students of the control group show slight improvement which is 6,36 on pre-test classified as Fair to 7,91 on post-test classified as Good after given treatment using the conventional method. It means enhancing students’ vocabulary mastery using Spot It! Card Game is more effective than using the conventional methods in distance learning.